Silicon nitride powder and its manufacturing method, and method for manufacturing sintered silicon nitride
By producing silicon nitride powder with reduced impurities through controlled reductive nitriding, the silicon nitride sintered bodies achieve improved high-temperature strength and uniformity, addressing the densification challenges of existing technologies.
Patent Information
- Application Number
- JP2021522821
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-30
- Filing Date
- 2020-05-27
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2040-05-27
AI Technical Summary
Silicon nitride sintered bodies used in high-temperature environments require excellent high-temperature strength, which is hindered by impurities in the raw material powder, particularly oxygen, fluorine, and chlorine, affecting densification and microstructure uniformity.
Production of silicon nitride powder with reduced impurities (oxygen ≤ 3.0% by mass, fluorine and chlorine ≤ 25 mass ppm) through a reductive nitriding process, promoting grain growth and uniform microstructure by controlling firing conditions and raw material blending.
The resulting silicon nitride sintered bodies exhibit enhanced high-temperature strength and uniformity, suitable for applications like gas turbines and power modules, achieved at a lower manufacturing cost.
Smart Images

Figure 0007620545000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a silicon nitride powder and a method for producing the same, and a method for producing a silicon nitride sintered body. [Background technology]
[0002] Silicon nitride is a material that is excellent in strength, hardness, toughness, heat resistance, corrosion resistance, thermal shock resistance, etc. For this reason, the use of silicon nitride sintered bodies as insulating substrates for machine parts such as gas turbines, turbo rotors, and valves, and power modules for automobiles, machine tools, etc. is being considered. Silicon nitride sintered bodies used for these applications are required to have a dense and homogeneous structure. In order to produce such silicon nitride sintered bodies, a technology for providing a high-purity and homogeneous silicon nitride powder is being considered.
[0003] Known methods for synthesizing silicon nitride powder include a direct nitridation method (direct reaction method) in which metal silicon powder is nitrided in a mixed atmosphere of hydrogen gas or ammonia gas and nitrogen gas, a reduction nitridation method of silica powder, and an imide decomposition method. Patent Document 1 proposes a method for producing silicon nitride powder with a high content of α-type Si3N4. Patent Document 2 proposes the production of silicon nitride powder with fewer impurities by the imide decomposition method. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 7-81910 [Patent Document 2] JP 2000-302421 A Summary of the Invention [Problem to be solved by the invention]
[0005] Silicon nitride sintered bodies are required to have excellent strength at high temperatures (high-temperature strength) because they are sometimes used in high-temperature environments. It is believed that the silicon nitride sintered body needs to be densified in order to improve high-temperature strength. A factor that hinders the densification of silicon nitride sintered bodies is thought to be the influence of impurities contained in the raw material, i.e., silicon nitride powder.
[0006] In view of this, the present disclosure provides a silicon nitride powder capable of producing a silicon nitride sintered body having excellent high-temperature strength by reducing impurities. It also provides a method for producing a silicon nitride powder capable of producing a silicon nitride powder with sufficiently reduced impurities at low production cost. It also provides a method for producing a silicon nitride sintered body capable of producing a silicon nitride sintered body having excellent high-temperature strength at low production cost. [Means for solving the problem]
[0007] The silicon nitride powder according to one aspect of the present disclosure has an oxygen content of 3.0 mass% or less and a total fluorine and chlorine content of 25 mass ppm or less. Since the contents of oxygen, fluorine and chlorine, which affect high-temperature strength, are sufficiently low in such silicon nitride powder, a silicon nitride sintered body having excellent high-temperature strength can be produced.
[0008] The silicon nitride powder preferably has an alpha-phase ratio of 92 mass% or more. A high alpha-phase ratio can promote grain growth during sintering of the silicon nitride powder. This allows a sufficiently dense silicon nitride sintered body to be produced. Therefore, a silicon nitride sintered body having even better high-temperature strength can be obtained.
[0009] In the silicon nitride powder, the ratio of primary particles having a particle size of 2 μm or more is preferably 2% or less. This makes it possible to make the microstructure of the silicon nitride sintered body obtained by sintering the silicon nitride powder more uniform. As a result, it is possible to obtain a silicon nitride sintered body having even better high-temperature strength.
[0010] The method for producing silicon nitride powder according to one aspect of the present disclosure includes a calcination step in which raw powder containing silica powder, carbon powder, and silicon nitride seed crystals is calcined in a nitrogen atmosphere at 1300 to 1550 ° C for 50 hours or more to obtain silicon nitride powder. In this production method, the raw powder is calcined at 1300 to 1550 ° C for a sufficiently long time in the calcination step, so that the reduction-nitridation reaction of the silica powder proceeds sufficiently. Therefore, silicon nitride powder with sufficiently reduced impurities can be produced. This production method can reduce the production cost of silicon nitride powder compared to the imide method. In addition, in the direct nitridation method, pulverization is usually required to pulverize the powder, but acid treatment is required to reduce impurities derived from pulverization. In this case, the chemical components of the acid treatment remain and become impurities. Therefore, according to the method for producing silicon nitride powder of the present disclosure, silicon nitride powder with sufficiently reduced impurities can be produced at a low production cost.
[0011] The silicon nitride powder obtained by the above-mentioned firing step preferably has an oxygen content of 3.0 mass% or less and a total content of fluorine and chlorine of 25 mass ppm or less. By using such silicon nitride powder, a silicon nitride sintered body having excellent high-temperature strength can be produced.
[0012] The silicon nitride powder obtained by the above-mentioned firing step preferably has a ratio of primary particles having a particle size of 2 μm or more of 2% or less. This makes it possible to make the microstructure of the silicon nitride sintered body obtained by firing the silicon nitride powder more uniform. Therefore, it is possible to obtain a silicon nitride sintered body having better high-temperature strength. The ratio of primary particles described above in this disclosure is based on the number of particles.
[0013] A method for producing a silicon nitride sintered body according to one aspect of the present disclosure includes a sintering step of sintering any of the silicon nitride powders described above or any of the silicon nitride powders obtained by any of the production methods described above to obtain a silicon nitride sintered body. In this production method, silicon nitride powder with reduced impurities is sintered, so that a silicon nitride sintered body having excellent high-temperature strength can be produced. Effect of the Invention
[0014] According to the present disclosure, it is possible to provide a silicon nitride powder capable of producing a silicon nitride sintered body having excellent high-temperature strength by reducing impurities. It is also possible to provide a method for producing a silicon nitride powder capable of producing a silicon nitride powder having a sufficiently reduced impurity content at low production cost. It is also possible to provide a method for producing a silicon nitride sintered body capable of producing a silicon nitride sintered body having excellent high-temperature strength at low production cost. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, one embodiment of the present disclosure will be described. However, the following embodiment is an example for explaining the present disclosure, and is not intended to limit the present disclosure to the following content.
[0016] The silicon nitride powder according to one embodiment has an oxygen content of 3.0 mass% or less, and a total content of fluorine and chlorine of 25 mass ppm or less. From the viewpoint of being able to produce a silicon nitride sintered body having even better high-temperature strength, the oxygen content may be 2.5 mass% or less, 2.3 mass% or less, or 1.8 mass% or less. By reducing the oxygen content of the silicon nitride powder, it is possible to reduce internal defects of the silicon nitride sintered body obtained by sintering the silicon nitride powder. This makes it possible to obtain a silicon nitride sintered body having sufficiently high high-temperature strength. The oxygen content tends to depend on the firing time when producing the silicon nitride powder and the blending ratio of carbon powder in the starting material used when producing the silicon nitride powder.
[0017] The oxygen content of the silicon nitride powder may be 0.1% by mass or more, or 0.5% by mass or more, from the viewpoint of reducing the manufacturing cost of the silicon nitride powder. An example of the oxygen content of the silicon nitride powder may be 0.1 to 3.0% by mass, or 0.5 to 2.5% by mass. The oxygen content of the silicon nitride powder can be measured using a commercially available oxygen / nitrogen analyzer. The measurement is performed in a helium gas atmosphere by continuously increasing the temperature from 20°C to 3000°C. The oxygen content can be quantified from the area of the peak resulting from the desorption of oxygen in the obtained measurement results.
[0018] The total content of fluorine and chlorine in the silicon nitride powder may be 22 mass ppm or less, 20 mass ppm or less, or 19 mass ppm or less, from the viewpoint of being able to produce a silicon nitride sintered body having even better high-temperature strength. By reducing the total content of fluorine and chlorine in the silicon nitride powder, the fluorine and chlorine contained in the grain boundary phase of the silicon nitride sintered body obtained by sintering the silicon nitride powder is reduced. Therefore, the grain boundary phase of the silicon nitride sintered body can be suppressed from softening at high temperatures. Therefore, it is possible to obtain a silicon nitride sintered body having sufficiently high high-temperature strength. The total content of fluorine and chlorine tends to depend on the purity of the starting material used in producing the silicon nitride powder, the compounding ratio of the silica powder and the carbon powder (C / SiO2), the firing time, and the presence or absence of post-treatment (washing) after firing, etc.
[0019] For example, if the compounding ratio (C / SiO2) of silica powder and carbon powder when preparing the raw material powder is too small, the desorption of SiCl4 due to the reaction of SiO2 or SiO with Cl2 tends to be difficult to proceed. The same tendency also occurs when the firing time is too short.
[0020] The total content of fluorine and chlorine in the silicon nitride powder may be 1 mass ppm or more, or 5 mass ppm or more, from the viewpoint of reducing the manufacturing cost of the silicon nitride powder. The total content of fluorine and chlorine in the silicon nitride powder may be, for example, 1 to 25 mass ppm, or 5 to 22 mass ppm. The total content of fluorine and chlorine in the silicon nitride powder can be measured by heating the silicon nitride powder and quantifying the fluorine and chlorine contained in the generated gas by ion chromatography.
[0021] The alpha-phase rate of the silicon nitride powder may be 92% by mass or more, 95% by mass or more, or 96% by mass or more. By having a high alpha-phase rate, grain growth can be promoted during sintering of the silicon nitride powder. This makes it possible to produce a sufficiently densified silicon nitride sintered body. Therefore, it is possible to obtain a silicon nitride sintered body having even better high-temperature strength.
[0022] The alpha-phase ratio of the silicon nitride powder may be 99% by mass or less, or 98% by mass or less, from the viewpoint of reducing the manufacturing cost of the silicon nitride powder. For example, the alpha-phase ratio of the silicon nitride powder may be 92 to 99% by mass, 95 to 99% by mass, or 96 to 98% by mass. The alpha-phase ratio of the silicon nitride powder can be determined based on the diffraction line intensity of X-ray diffraction.
[0023] The proportion of primary particles having a particle size of 2 μm or more among the primary particles contained in the silicon nitride powder is preferably 2% or less. This proportion may be 1% or less, or may be 0.5% or less. By reducing this proportion, the microstructure of the silicon nitride sintered body obtained by sintering the silicon nitride powder can be made more uniform. Therefore, a silicon nitride sintered body having even better high-temperature strength can be obtained.
[0024] The proportion of primary particles having a particle size of 2 μm or more among the primary particles contained in the silicon nitride powder may be 0.1% or more, or may be 0.3% or more, from the viewpoint of reducing the manufacturing cost of the silicon nitride powder. One example of the proportion may be 0.1 to 2%, or may be 0.3 to 1%. The proportion is a proportion based on the number of particles, and can be determined based on the particle size distribution measured by importing an image taken by a scanning electron microscope into image analysis type particle size distribution measurement software.
[0025] The silicon nitride powder may contain carbon or carbide as a component other than silicon nitride. The total content of carbon and carbide in the silicon nitride powder is preferably 10 mass% or less, more preferably 7 mass% or less, calculated as carbon.
[0026] The method for producing silicon nitride powder according to one embodiment includes a blending step of blending silica powder, carbon powder, and silicon nitride seed crystals to prepare a raw material powder, and a firing step of firing the raw material powder in a nitrogen atmosphere at 1300 to 1550°C for 50 hours or more to obtain silicon nitride powder. The firing time may be, for example, 200 hours or less from the viewpoint of production efficiency. Examples of silica powder include fused silica powder, crystalline silica powder, and silicate compounds. Examples of carbon powder include acetylene black, furnace black, channel black, and graphite. The silicon nitride used as the seed crystals preferably has a high alpha conversion rate (for example, an alpha conversion rate of 90% or more) from the viewpoint of increasing sinterability.
[0027] The compounding ratio of the carbon powder to the silica powder in the compounding step may be 2.0 to 3.8, or 3.0 to 3.7, on a molar basis (C / SiO2) from the viewpoint of obtaining silicon nitride powder in which the total content of fluorine and chlorine and the oxygen content are sufficiently reduced. The compounding amount of the silicon nitride seed crystals per 100 parts by mass of the silica powder may be 10 to 20 parts by mass, or 11 to 18 parts by mass, from the viewpoint of obtaining silicon nitride powder with sufficiently high purity while reducing production costs.
[0028] The total content of fluorine and chlorine in the raw material powder is preferably 50 mass ppm or less, more preferably 40 mass ppm or less, from the viewpoint of sufficiently reducing the total content of fluorine and chlorine in the silicon nitride powder produced. On the other hand, the total content of fluorine and chlorine in the raw material powder may be 10 mass ppm or more, or may be 20 mass ppm or more, from the viewpoint of reducing the production cost of the silicon nitride powder.
[0029] In the firing step, the raw material powder is fired using, for example, an electric furnace, whereby the following reaction formula (1) proceeds. From the viewpoint of sufficiently proceeding with the reaction of reaction formula (1), the firing temperature may be 1450 to 1550°C. From the viewpoint of sufficiently proceeding with the reduction-nitridation reaction of the silica powder, the firing time may be 150 hours or more, or may be 200 hours or more. On the other hand, from the viewpoint of reducing the production cost of the silicon nitride powder, the firing time may be 500 hours or less, or may be 400 hours or less. 3SiO2+6C+2N2→Si3N4+6CO↑ (1)
[0030] The firing step is carried out in a nitrogen atmosphere. The oxygen concentration in the nitrogen atmosphere may be 100 ppm by volume or less, or may be 20 ppm by volume or less. By sufficiently lowering the oxygen concentration in the nitrogen atmosphere, the oxygen content of the silicon nitride powder produced can be further reduced. When the silicon nitride powder contains carbon or carbide, a decarburization step may be carried out. The decarburization step can be carried out, for example, by heating the silicon nitride powder to 650 to 900°C in the air. This can reduce the total content of carbon and carbide in the silicon nitride powder.
[0031] According to the above-mentioned manufacturing method, the silicon nitride powder according to the above-mentioned embodiment can be obtained. Examples of properties such as the oxygen content, the total content of fluorine and chlorine, the alpha conversion rate, and the particle size of the silicon nitride powder are as described above. In the manufacturing method of the silicon nitride powder of the present embodiment, the silicon nitride powder is manufactured by a reduction-nitridation reaction of the silica powder. Therefore, the manufacturing cost of the silicon nitride powder can be reduced compared to the imide method. In addition, in the direct nitridation method, pulverization is usually required for fine powdering, but acid treatment is required to reduce impurities derived from pulverization. In this case, the chemical components of the acid treatment remain and become impurities. Therefore, according to the manufacturing method of the silicon nitride powder of the present disclosure, the silicon nitride powder with sufficiently reduced impurities can be manufactured at a low manufacturing cost.
[0032] The method for producing a silicon nitride sintered body according to one embodiment includes a sintering step of sintering the silicon nitride powder according to the above embodiment to obtain a silicon nitride sintered body. In this production method, for example, the silicon nitride powder is pressed at a molding pressure of, for example, 3.0 to 10.0 MPa to obtain a molded body. The molded body may be produced by uniaxial pressing or by CIP. Also, it may be sintered while being molded by hot pressing.
[0033] The sintering of the molded body may be carried out in an inert gas atmosphere such as nitrogen gas or argon gas. The pressure during sintering may be 0.7 to 0.9 MPa. The sintering temperature may be 1700 to 1900°C. The sintering time at the sintering temperature may be 4 to 20 hours, or 8 to 16 hours. The rate of temperature rise to the sintering temperature may be, for example, 1.0 to 10.0°C / hour.
[0034] The silicon nitride sintered body thus obtained has a sufficiently reduced oxygen content and a sufficiently reduced total content of fluorine and chlorine. Since the oxygen content is sufficiently reduced, defects occurring inside the silicon nitride sintered body can be suppressed. Therefore, the silicon nitride sintered body has excellent high-temperature strength as well as insulation and thermal conductivity. Defects contained in the silicon nitride sintered body include lattice defects such as dislocations and pores. In addition, since the total content of fluorine and chlorine is sufficiently reduced, the grain boundary phase of the silicon nitride sintered body can be suppressed from softening at high temperatures. Therefore, a silicon nitride sintered body having sufficiently high high-temperature strength can be obtained.
[0035] In the present disclosure, high-temperature strength refers to strength at 1300°C. A silicon nitride sintered body having high strength in such a temperature range can be particularly suitably used for applications such as gas turbines, power modules for automobiles, and bearings. The bending strength of the silicon nitride sintered body according to one embodiment at a temperature of 1300°C may be, for example, 700 MPa or more, or may be 750 MPa or more. This strength is a four-point bending strength (1300°C) measured using a commercially available measuring device.
[0036] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. For example, the silicon nitride powder may be used for purposes other than the manufacture of a silicon nitride sintered body. EXAMPLES
[0037] The present disclosure will be described in more detail with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0038] <Preparation of silicon nitride powder> Example 1 A raw material powder was obtained by blending fused silica powder (particle size: 0.6 μm), acetylene black powder, and silicon nitride powder (seed crystals). The total content of fluorine and chlorine in the raw material powder was 40 ppm by mass. The blending ratio (mass basis) was fused silica powder: acetylene black powder: silicon nitride powder = 55.2%: 38.5%: 6.3%. The molar ratio of acetylene black to fused silica powder (C / SiO2) was 3.5. 320 g of this raw material powder was filled into a 2 L polyethylene container, silicon nitride balls (φ: 15 mm) were added, and the mixture was mixed in a ball mill for 2 hours.
[0039] The raw material powder was fired in an electric furnace in a nitrogen atmosphere at atmospheric pressure at 1500°C for 60 hours to obtain a lump of nitride. The nitride was crushed in a silicon nitride mortar to obtain nitride powder. This was placed in an alumina crucible and heated in an electric furnace at 800°C for 3 hours to decarburize. The decarburized powder obtained by decarburization was filled into an alumina pot together with silicon nitride balls and pulverized in a vibration mill for 3 hours to obtain silicon nitride powder.
[0040] Example 2 Silicon nitride powder was obtained in the same manner as in Example 1, except that the time for firing the raw material powder at 1500° C. was changed from 60 hours to 110 hours.
[0041] Comparative Example 1 Silicon nitride powder was obtained in the same manner as in Example 1, except that the time for firing the raw material powder at 1500° C. was changed from 60 hours to 10 hours.
[0042] Comparative Example 2 A silicon nitride powder was obtained in the same manner as in Example 2, except that the blending ratio (mass basis) of fused silica powder: acetylene black powder: silicon nitride powder was 52.3%: 41.7%: 6.0%. The molar ratio of acetylene black to fused silica powder (C / SiO2) was 4.0.
[0043] Comparative Example 3 Silicon nitride powder was obtained in the same manner as in Example 1, except that the time for firing the raw material powder at 1500° C. was changed from 60 hours to 5 hours.
[0044] <Evaluation of silicon nitride powder> The oxygen content in the silicon nitride powder of each Example and Comparative Example was measured by the following procedure. The crucible containing the graphite powder was degassed using an oxygen / nitrogen analyzer (manufactured by Horiba, Ltd., device name: EMGA-920W). The prepared silicon nitride powder was weighed and mixed with the graphite powder in the crucible. Thereafter, the temperature was raised from 20°C to 2300°C in a helium gas atmosphere, and the oxygen generated with the temperature rise was detected. The amount of oxygen contained in the silicon nitride powder was quantified from the peak area resulting from the desorption of oxygen. The measurement results are shown in Table 1.
[0045] The total content of fluorine and chlorine contained in the silicon nitride powder was measured by the following procedure. The silicon nitride powder was heated using an automatic sample combustion device (manufactured by Mitsubishi Chemical Corporation, device name: AQF-2100H type), and the generated gas was dissolved in water. The fluorine and chlorine dissolved in water were measured using an ion chromatograph (manufactured by Thermo Fisher Scientific, device name: ICS-2100) in accordance with JIS R 1603:2007. Based on this measured value, the fluorine and chlorine contained in the silicon nitride powder were quantified. The measurement results are shown in Table 1. In Table 1, "halogen content" refers to the total content of fluorine and chlorine.
[0046] The alpha phase ratio of the prepared silicon nitride powder was measured by the following procedure. X-ray diffraction of the silicon nitride powder was performed using an X-ray diffractometer (Rigaku, device name: Ultima IV) with CuKα radiation. The alpha phase was determined by the diffraction intensity I a102 and the (210) diffraction intensity I a210 , β phase has a diffraction intensity of I b101 and the (210) diffraction intensity I b210 Using these diffraction intensities, the gelatinization rate was calculated according to the following formula. The results are shown in Table 1. Alpha conversion rate (mass%) = (Ia102 +I a210 ) / (I a102 +I a210 +I b101 +I b210 ) x 100
[0047] The proportion of particles with a particle size of 2 μm or more contained in the prepared silicon nitride powder was measured by the following procedure. Using a scanning electron microscope (manufactured by JEOL Ltd., device name: JSM-6301F), the silicon nitride powder was observed at 5000 times magnification and images were taken (field of view: 16 μm × 23 μm). The images taken were imported into image analysis type particle size distribution measurement software (manufactured by Mountec Co., Ltd., product name: Mac View version 4.0) and the particle size distribution was measured. From the measurement results, the proportion of primary particles with a particle size of 2 μm or more was calculated. The results are shown in Table 1.
[0048] <Preparation of sintered silicon nitride> The silicon nitride powders of each Example and Comparative Example were each uniaxially pressed to produce a cylindrical molded body. The molded body was placed in an electric furnace equipped with a carbon heater and heated to 1850°C in a nitrogen atmosphere. After sintering at 1850°C for 6 hours, the body was cooled to obtain a silicon nitride sintered body.
[0049] <Evaluation of sintered silicon nitride> The density (20°C) and four-point bending strength at 1300°C of the obtained silicon nitride sintered body were measured. The density was measured by Archimedes' method. The four-point bending strength at 1300°C was measured using an autograph AG-2000 (product name) manufactured by Shimadzu Corporation. The relative values of the density and four-point bending strength based on the measurement results of the silicon nitride sintered body produced using the silicon nitride powder of Example 1 were as shown in Table 1.
[0050] [Table 1]
[0051] Comparative Examples 1 and 3, which had a higher oxygen content than Examples 1 and 2, had lower high-temperature strength than Examples 1 and 2. Comparative Example 2, which had a higher total fluorine and chlorine content than Examples 1 and 2, also had lower high-temperature strength than Examples 1 and 2. As shown in Table 1, it was confirmed that by using silicon nitride powder with a low oxygen content and a low total fluorine and chlorine content, a silicon nitride sintered body with excellent high-temperature strength can be obtained. [Industrial Applicability]
[0052] According to the present disclosure, it is possible to provide a silicon nitride powder capable of producing a silicon nitride sintered body having excellent high-temperature strength by reducing impurities. It is also possible to provide a method for producing a silicon nitride powder capable of producing a silicon nitride powder having a sufficiently reduced impurity content at low production cost. It is also possible to provide a method for producing a silicon nitride sintered body capable of producing a silicon nitride sintered body having excellent high-temperature strength at low production cost.
Claims
1. The oxygen content is 1.2 to 3.0 mass%, the total content of fluorine and chlorine is 22 mass ppm or less, and the proportion of primary particles having a particle size of 2 μm or more is 2% or less, A silicon nitride powder containing carbon or carbide, the total content of carbon and carbide being 7 mass% or less.
2. 2. The silicon nitride powder according to claim 1, having an gelatinization rate of 92 mass % or more.
3. 3. The silicon nitride powder according to claim 1, wherein the total content of fluorine and chlorine is 1 to 20 ppm by mass.
4. A firing step of firing a raw material powder containing silica powder, carbon powder, and silicon nitride seed crystals in a nitrogen atmosphere at 1300 to 1550° C. for 50 hours or more to obtain silicon nitride powder, A method for producing silicon nitride powder, wherein the silicon nitride powder obtained in the firing step has an oxygen content of 3.0 mass% or less, and a total fluorine and chlorine content of 25 mass ppm or less.
5. 5. The method for producing silicon nitride powder according to claim 4, wherein the silicon nitride powder obtained in the firing step has an oxygen content of 1.2 to 3.0 mass%, and a total content of fluorine and chlorine of 22 mass ppm or less.
6. 6. The method for producing silicon nitride powder according to claim 4, wherein the silicon nitride powder obtained in the firing step has a ratio of primary particles having a particle size of 2 μm or more of 2% or less.
7. A method for producing a silicon nitride sintered body, comprising a sintering step of sintering the silicon nitride powder according to any one of claims 1 to 3 to obtain a silicon nitride sintered body.
8. A method for producing a silicon nitride sintered body, comprising a sintering step of firing the silicon nitride powder obtained by the method according to any one of claims 4 to 6 to obtain a silicon nitride sintered body.
Citation Information
Patent Citations
Apparatus for printing passbooks
JP1987001564A
Production of easy-to-sinter high-purity silicon nitride fine powder
JP1988040709A
Production of fine particles of high-purity silicon nitride
JP1993310405A
Production of high alpha-type silicon nitride
JP1995081910A
Silicon nitride powder and its production
JP1995206409A